Different Times for Different Metrics: Predicting 90 Days of Intermittently Scanned Continuous Glucose Monitoring Data in Subjects With Type 1 Diabetes on Multiple Daily Injection Therapy. Findings From a Multicentric Real-World Study - Csermely, Alessandro; Borella, Nicolò D; Turazzini, Anna; Pilati, Martina; Sheiban, Sara S; Bonadonna, Riccardo C; Trevisan, Roberto; Trombetta, Maddalena; Lepore, Giuseppe (Journal of diabetes science and technology, 2025)
According to the 2023 International Consensus, glucose metrics derived from two-week-long continuous glucose monitoring (CGM) can be extrapolated up to 90 days before. However, no studies have focused on adults with type 1 diabetes (T1D) on multiple daily injections (MDIs) and with second-generation intermittently scanned CGM (isCGM) sensors in a real-world setting. This real-world, retrospective study included 539 90-day isCGM data from 367 adults with T1D on MDI therapy. For each sensor metric, the coefficients of determination ( ) were computed for sampling periods from 2 to 12 weeks versus the whole 90-day interval. Correlations were considered strong for ≥0.88. The two-week sampling period displayed strong correlations for time in range (TIR, 70-180 mg/dl; = 0.89) and above range (TAR, >180 mg/dl; = 0.88). The four-week sampling period showed additional strong correlations for time in tight range (TITR, 70-140 mg/dl; = 0.92), for the coefficient of variation (CV; = 0.88), and for the glycemia risk index (GRI; = 0.92). The six-week sampling period displayed an additional strong correlation for time below range (TBR, <70 mg/dl; = 0.90). After stratification by clinical variables, lower values were found for older age quartiles (>40 years), higher CV (>36%), lower sensor use (≤94%), and higher HbA1c (>7.5%). In patients with T1D on MDI, two- to six-week intervals of isCGM use can provide clinically useful estimates of TIR, TAR, TITR, TBR, CV, and GRI, which can be extrapolated to longer (up to 90 days) time intervals. Longer intervals might be needed in case of older age, higher glucose variability, lower sensor use, and higher HbA1c.